Kinerja Keuangan PT Industri Jamu dan Farmasi Sido Muncul,TBK Periode 2017-2021 - Haris, Nurhayati; Alfrianti, Alda; Yamin, Nina Yusnita; Natsir, Muhammad; Usman, Ernawaty; Kamase, Haryono Pasang (Politeknik Negeri Ambon, 2024)
The purpose of this research is to describe and analyze the financial performance of PT Industri Jamu dan Farmasi Sido Muncul,Tbk for the period 2017-2021. The research method used is quantiative descriptive, using financial ratio analysis and trend analysis. The research data used is financial reports. The results of reseacrh on financial ratio analysis show the financial performance of PT Industri Jamu dan Farmasi Sido Muncul,Tbk for the 2017-2021 periode as a whole is in goos condition except for the receivable turnover ratio which has experienced an increase which shows that the company is not good at managing it’s receivable. The results of the trend analysis show that the financial performance of PT Industri Jamu dan Farmasi Sido Muncul,Tbk for the period 2017-2021 tends to decrease in terms of current ratio, cash ratio, dan receivables turnover.The debt to asset ratio and debt to equity ratio are experiencing an increasing trend, this condition is not good because the company debt burden is increasing every year. Total asset turnover, net profit margin, and return on investment tend to increase, indicating better managemen of total assets. So that company gets better profits every year. Keywords: Finacial Performance, Liquidity, Activity, Solvency, Profitability